Family resilience in patients with gynecological malignant tumors after radical hysterectomy: based on the Walsh family resilience framework - Zhang, Xinru; Li, Xi; Wang, Xindi; Chen, Yiteng; Guo, Yu; Ruan, Weiqing (Frontiers in Oncology, 2025)
AimExplore and analyze the family resilience of patients with gynecological malignancies after radical hysterectomy, providing a theoretical basis for the formulation of future intervention measures.MethodsUsing a phenomenological descriptive qualitative research method, 17 patients who underwent radical surgery for gynecological malignancies were selected for semi-structured interviews. Data analysis and theme extraction were conducted using Colaizzi data analysis method and NVivo V.12.ResultsThree themes and eight sub-themes were extracted: family belief system (confront surgical challenges head-on, attribute positive significance to adversity, stay positive), family organization model (timely adjustment of family roles, family cohesion, get support and help from others), and family communication and problem solving skills (communicate to eliminate negative emotions, collaborative problem solving).ConclusionThis study indicates that the family belief system is the solid foundation of family resilience, the family organizational pattern serves as a buffer when the family faces adversity, and positive communication and collaborative problem solving create a positive feedback loop that enhances family resilience. Future interventions could enhance patients’ family resilience from the perspective of family strengths.